On numerical investigation of heat transfer augmentation of flat target surface under impingement of steady air jet for varying heat flux boundary condition - Siddique, Umair M; Syed, Ashfaq; Khan, Sher Afghan; Meyer, Josua P. (Springer Nature, 2021)
The prediction of flow pattern for the proposed range of Reynolds number and nozzle–target spacing is carried out using SST + Gamma–Theta turbulence model. The simulations of the flow field in a computational domain are carried out using CFX as a base solver with 10−6 being the converging criteria. The present work aims to determine the local Nusselt number magnitude for varying heat flux input boundary conditions. Not only this, the impinging Reynolds numbers and nozzle–target spacing are also varied to record sufficient data, enough to predict a semi-empirical correlation. The proposed correlation for calculating the cooling characteristic (Nusselt number magnitude) under the impingement of air jet is presented in terms of profile heat flux parameter, impinging Reynolds number, and target to nozzle exit spacing. The corresponding mathematical parameter representing the profile heat flux boundary condition is the slope in heat flux magnitude versus the target surface’s radial distance. The Nusselt number profile, which describes the cooling characteristic under different impinging Reynolds numbers and nozzle–target spacing, initially increases, takes a peek, and decreases. The rise in the cooling rate near the stagnation region is due to the turbulence palpitation, resulting from imbalance adverse pressure gradient and onset transition of Reynolds number. The local heat transfer under such boundary conditions increases with nozzle–target spacing and least depends on Reynolds number. However, the Nusselt profile for a constant heat flux magnitude but the varying slope (non-uniform) shows an enhancement with a decrease in the slope from unit value.